51 L-Arginine ameliorates the progression of autoimmune myocarditis. (19th December 2016) - Zheng, Kai; Han, Lina; Guo, Shuli; Wang, Zhenyu; Dong, Xinghui
Abstract : Objectives: Nitric oxide (NO) plays a dual role: it can inhibit the inflammatory process under physiological conditions, but on the other hand, a large amount of NO can be involved in inflammation in autoimmune myocarditis. We investigated the effects of N-nitro-L-arginine methyl ester (L-NAME), an inducible nitric oxide synthase (iNOS) inhibitor, in the treatment of BALB/c mice with experimental autoimmune myocarditis (EAM) and discuss the therapeutic mitochondrial mechanism induced by apoptosis. Methods: Sixty male BALB/c mice aged 4–5 weeks were randomly divided into a normal control group, a model control group and an experimental group. EAM was induced in the model control group and experimental group by injection of porcine cardiac myosin subcutaneously into the groin and axilla and intraperitoneal injection of pertussis toxin on days 0 and 7, respectively. The model control group was intraperitoneally administered 5 mg/kg/day of physiological saline after injection of myosin and pertussis toxin. The experimental group was intraperitoneally given 5 mg/kg/day of L-NAME on days 1–21. At the end of the intervention, mice were euthanatized and hearts were harvested on day 21. The inflammatory score, fibrosis score, protein expression levels of caspase-3, caspase-8 and caspase-9, serum NO level, iNOS, iNOS mRNA, caspase-3, caspase-8 and caspase-9 mRNA, cardiac reactive oxygen species (ROS) production rate and mitochondrial membrane potential were measured. Mouse heart weight/body weight was calculated (HW/BW). Results: The inflammatory score, cardiac interstitial fibrosis score, cardiac apoptotic index, protein expression levels of caspase-3, caspase-8 and caspase-9, HW/BW, level of NO and activity of iNOS, expression levels of iNOS mRNA, and caspase-3, caspase-8 and caspase-9 protein were all significantly higher in the model control group and experimental group than in the normal control group (p < 0.01), and the levels in the model control group were higher than in the experimental group. HW/BW was only slightly elevated in the model control group compared with the experimental group. Conclusions: The development of EAM is related to the NO catalyzed by iNOS. L-NAME protected cardiac myocytes through suppressing the activity of iNOS and further decreased production of NO in EAM. The mechanism may be related to inhibiting the apoptosis of cardiac myocytes mediated by the caspase family and protecting mitochondrial function. Acknowledgments: This research was financially supported by the National Natural Science Foundation (Grant No. 61573139).